Measurement of StO2 Prehospital and Lactate Levels on the Arrival at the Hospital: Observational Study in Mountain Traumatology (London Journal of Medical and Health Research, 2023)
Hypovolemia is a major complication of trauma patients, leading, if not treated rapidly, to tissue and organ hypo perfusion and the development of multiple organ failure. During the out of hospital management of trauma patients, it is recommended to maintain the blood pressure in first time with the fluid administration and if it is not sufficient in second time by a vasopressor. The aim of these treatments is to avoid microcirculation alteration with a deficit of tissue perfusion and oxygen delivery to vital organs. In trauma patients, peripheral muscle tissue oxygen saturation (StO2) measured by near-infrared spectroscopy (NIRS) was shown to be more reliable than systemic hemodynamic variables as an index of severity of traumatic shock.The objective of this prospective study was to compare hemodynamic variables and the lactate values with the regional tissue oxygenation satur- ation monitoring (StO2) measured by near-infrared spectroscopy in the prehospital management of mountain trauma patients.
Keywords: prehospital microvascular management - StO2 - NIRS - lactate - mountain traumatology